Association Between Maternal Body Mass Index in Early Pregnancy and Incidence of Cerebral Palsy. Issue 8 (August 2017) - Villamor, Eduardo; Tedroff, Kristina; Peterson, Mark; Johansson, Stefan; Neovius, Martin; Petersson, Gunnar; Cnattingius, Sven
Abstract : (Abstracted from JAMA 2017;317(9):925–936) Prevalence of cerebral palsy (CP) rose between 1998 and 2006, and few preventable risk factors are known for this most common pediatric motor disability. Maternal obesity, a risk factor for neonatal complications such as preterm delivery and asphyxia-related neonatal morbidities, has been suggested to be associated with CP.